A brief review of the shape memory phenomena in polymers and their typical sensor applications - Sun, Li (2019)
In this brief review, an introduction of the underlying mechanisms for the shape memory effect (SME) and various shape memory phenomena in polymers is presented first. After that, a summary of typical applications in sensors based on either heating or wetting activated shape recovery using largely commercial engineering polymers, which are programmed by means of in-plane pre-deformation (load applied in the length/width direction) or out-of-plane pre-deformation (load applied in the thickness direction), is presented. As demonstrated by a number of examples, many low-cost engineering polymers are well suited to, for instance, anti-counterfeit and over-heating/wetting monitoring applications via visual sensation and/or tactual sensation, and many existing technologies and products (e.g., holography, 3D printing, nano-imprinting, electro-spinning, lenticular lens, Fresnel lens, QR/bar code, Moiré pattern, FRID, structural coloring, etc.) can be integrated with the shape memory feature.